“History” as a Pet Subject of Theorists vs. What Historical Researchers Do (London Journal of Research In Humanities and Social Sciences, 2025)
The present article challenges both postmodern and later philosophy (or theory) of history for a neglect of analysis of what historical researchers actually do. Historical research is focussed on problems and their solutions, just as research of natural scientists. Theorists of history have since the 1960s tended to think that what historians do is equal to write history in a narrative form. Sometimes these theoreticians even deny the past as a reference. Neither these theorists nor newer anti-narrativist theorists (three examples are discussed) have examined what historical researchers do when they deal with problems and seek new knowledge. Finally, a brief discussion between two historical researchers (on Maos strategy) is analysed as an example of actual formation of new knowledge in history.
Keywords: Phenomenology; ASD; late modernity; complex phenomenon; psychotherapeutic discourse; medical discourse; psychotherapeutic discourse integrated into fiction; conceptual metaphor in therapy; agent and client of psychotherapeutic discourse; language representation of feelings and emotions.; existential psychoanalysis; Phenomenological clinic